(untitled) (Journal of Global Accounting, 2024)
The study examined the effect of audit quality on the financial performance of listed consumer goods companies in Nigeria. The specific objective was to determine the effect of audit fee, audit firm status, audit firm tenure and audit firm rotation on the cashflow return on investment. Ex-post facto research design was utilised in the study. Out of a population of twenty-one (21) listed consumer goods firms in Nigeria, purposive sampling was deployed to select a sample participant of fourteen (14) firms. Secondary data were manually collected from the financial reports of chosen firms over a span of 10 years (2013-2022). The hypothesis testing was conducted using panel data regression analysis with Panel Estimated Generalized Least Squares. The findings showed that: audit fee has a significant negative effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.0016); audit firm status has a significant positive effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.0001); audit firm tenure has a significant negative effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.0000); audit firm rotation has a significant negative effect on the cashflow return on investment of listed consumer goods firms in Nigeria (p-value = 0.0000). In conclusion, while high audit fees and long auditor tenures tend to negatively impact the financial performance of listed consumer goods firms in Nigeria, the reputation of the audit firm can have a beneficial effect; meanwhile, frequent audit firm rotation, despite its intended benefits, may also pose challenges to a company’s cashflow return on investment. The study recommends that board of directors should negotiate and monitor audit fees to ensure they are reasonable and commensurate with the scope of work required, avoiding unnecessary financial strain on the company’s resources.